2008
DOI: 10.1016/j.jnoncrysol.2007.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Normal and anti Meyer–Neldel rule in conductivity of highly crystallized undoped microcrystalline silicon films

Abstract: We have studied the electrical conductivity behavior of highly crystallized undoped hydrogenated microcrystalline silicon (lc-Si:H) films having different microstructures. The dark conductivity is seen to follow Meyer-Neldel rule (MNR) in some films and anti-MNR in others, which has been explained on the basis of variation in the film microstructure and the corresponding changes in the effective density of states distributions. A band tail transport and statistical shift of Fermi level are used to explain the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…The behavior of the activation energy and 0 as a function of crystallinity within the model is in qualitative agreement with experimental observations, like those of Kočka et al 10 and Ram et al, 28 if we assume that the condition , which is lower than reported oxygen concentrations in some device grade materials. 11 The defect density derived in this way is 10 16 cm −3 , which is a typical value for spin densities in ESR experiments, 31 but we have to keep in mind that the spread in properties of these materials can be large and it is suggested that high spin densities at high X c are related to surface effects.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The behavior of the activation energy and 0 as a function of crystallinity within the model is in qualitative agreement with experimental observations, like those of Kočka et al 10 and Ram et al, 28 if we assume that the condition , which is lower than reported oxygen concentrations in some device grade materials. 11 The defect density derived in this way is 10 16 cm −3 , which is a typical value for spin densities in ESR experiments, 31 but we have to keep in mind that the spread in properties of these materials can be large and it is suggested that high spin densities at high X c are related to surface effects.…”
Section: Discussionsupporting
confidence: 88%
“…For X c Ͼ X s 0 increases again, presumably because of a fast growing doping/dangling bond ratio. In experiments of Kočka et al 10 and Ram et al 28 E a is also decreasing for X c Ͼ X s , which leads to the experimentally observed inverse Meyer-Neldel rule ͑MNR͒. The lower E a could be explained by a decrease in the a-Si transport barriers between the nanocrystals.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations